The "Sardinian cold-water coral province" in the context of the Mediterranean coral ecosystems. (November 2017) - Taviani, M.; Angeletti, L.; Canese, S.; Cannas, R.; Cardone, F.; Cau, A.; Cau, A.B.; Follesa, M.C.; Marchese, F.; Montagna, P.; Tessarolo, C.
Abstract: A new cold-water coral (CWC) province has been identified in the Mediterranean Sea in the Capo Spartivento canyon system offshore the southern coast of Sardinia. The 'Sardinia cold-water coral province' is characterized in the Nora canyon by a spectacular coral growth dominated by the branching scleractinian Madrepora oculata at a depth of 380–460 m. The general biohermal frame is strengthened by the common occurrence of the solitary scleractinian Desmophyllum dianthus and the occasional presence of Lophelia pertusa . As documented by Remotely Operated Vehicle survey, this area is a hotspot of megafaunal diversity hosting among other also live specimens of the deep oyster Neopycnodonte zibrowii . The new coral province is located between the central Mediterranean CWC provinces (Bari Canyon, Santa Maria di Leuca, South Malta) and the western and northern ones (Melilla, Catalan-Provençal-Ligurian canyons). As for all the best developed CWC situations in the present Mediterranean Sea, the new Sardinian province is clearly influenced by Levantine Intermediate Water which appears to be a main driver for CWC distribution and viability in this basin.